Transient expression of keratin 19 is induced in originally negative interfollicular epidermal cells by adhesion of suspended cells - Dvořánková, Barbora; Smetana, Karel; Chovanec, Martin; Lacina, Lukáš; Štork, Jiří; Plzáková, Zuzana; Galovičová, Marianna; Gabius, H. J (International Journal of Molecular Medicine, 2005)
Keratin 19 and nuclear reactivity to an endogenous lectin, galectin-1, represent a potential marker of epidermal stem cells. We detected expression of keratin 19 and nuclear binding sites for galectin-1 in adult cells migrating from the hair follicle, where cells expressing keratin 19 are located in the bulge region. The results were compared with the expression of both markers in cells adhering from suspension prepared from the interfollicular epidermis without keratin-19-positive cells and with nuclear binding sites for galectin-1. The results were compared with data from basal cell carcinomas. All cells were analyzed concerning size, as it is known that cell diameter influences the clonogenic potential of keratinocytes. The major result of this study is the observation of transient expression of keratin 19 and nuclear galectin-1 binding sites in originally negative interfollicular epidermal cells induced by adhesion. These cells were very small in size, similar to basal cells of the interfollicular epidermis or the bulge region of the hair follicle. The influence of the suspension regimen on beta1-integrin expression, cell diameter and growth was also monitored. A population of cells highly positive for beta1 integrin of the same diameter as keratin-19-positive cells insensitive to induction of terminal differentiation by lack of anchorage was characterized. Cells of the same size were also observed in the keratin-19-positive cells of basal cell carcinomas. In conclusion, the expression of poor levels of differentiation induced by cell adhesion is transient. Also, keratin 19 expression should not be exclusively regarded as a marker of stem cell activity.
Keywords: galektin 3; financování organizované; keratinocyty; epidermis; Epidermis; galektin 1; Integrin beta1; Keratinocytes; bazocelulární karcinom; Keratins; Epidermal Cells; buněčná adheze; časové faktory; Time Factors; lidé; epidermální buňky; keratiny; Cell Adhesion; Intermediate Filament Proteins; vlasový folikul; kultivované buňky; Galectin 1; pohyb buněk; nádory kůže; Financing, Organized; Hair Follicle; Cells, Cultured; Galectin 3; Skin Neoplasms; Carcinoma, Basal Cell; buněčné kultury; Cell Movement; Cell Culture Techniques; proteiny intermediálních filament; antigeny CD29; Humans